Synthesis method and application of crystalline / amorphous cobalt manganese oxide catalyst

By using high-temperature calcining method of precursors such as cobalt acetylacetone and manganese acetylacetone and alkali metal salts during CO2 reduction, crystallized/amorphous CoMnOx catalysts were synthesized, and the problems of low catalyst activity and poor durability in the prior art were solved, and efficient CO2 reduction was achieved.

CN119524869APending Publication Date: 2025-02-28YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411636359.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing bimetal oxide photocatalysts have low catalyst activity during CO2 reduction, which makes it difficult to significantly improve the CO generation rate, and have poor durability and cycle stability.

Method used

Cobalt acetylacetonate and manganese acetylacetonate are used as metal precursors and alkali metal salts are used as reaction aids to synthesize crystallized/amorphous CoMnOx catalysts through high-temperature calcination. The calcination temperature is between the melting points of the metal precursor and the alkali metal salt to form a two-dimensional nanosheet structure and improve the photocatalytic activity of the catalyst.

Benefits of technology

The synthesized crystalline/amorphous cobalt-manganese oxygen catalyst exhibits good photocatalytic activity and catalytic stability in the photocatalytic CO2 reduction, significantly improving the CO production rate per unit time and improving the photocatalytic conversion efficiency of CO2-CO.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524869A_ABST
    Figure CN119524869A_ABST
Patent Text Reader

Abstract

The invention discloses a synthetic method of a crystalline / amorphous cobalt manganese oxide catalyst, which specifically comprises the following steps of: uniformly mixing cobalt acetylacetonate and manganese acetylacetonate serving as metal precursors and alkali metal salt serving as a reaction aid, calcining at high temperature, and washing and drying an obtained product after calcining to obtain crystalline / amorphous CoMnOx; wherein the calcination temperature is between the melting points of the metal precursor and the alkali metal salt. The invention also discloses an application of the crystalline / amorphous cobalt-manganese-oxygen catalyst prepared by the synthetic method in preparation of CO by photocatalytic reduction of CO2. The crystalline / amorphous cobalt manganese oxide catalyst prepared by the synthesis method has good photocatalytic activity and catalytic stability when applied to CO preparation by photocatalytic reduction of CO2, and can effectively improve the CO production rate in unit time, thereby greatly improving the photocatalytic conversion efficiency of CO2-CO. The invention also discloses an application of the crystalline / amorphous cobalt-manganese-oxygen catalyst prepared by the synthetic method in preparation of CO by photocatalytic reduction of CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for synthesizing a crystalline / amorphous cobalt manganese oxygen catalyst, and also relates to a method for synthesizing a crystalline / amorphous cobalt manganese oxygen catalyst prepared by the method in photocatalytic CO 2 Application in CO reduction. Background Art

[0002] Solar-driven CO 2 Catalytic conversion to produce high value-added carbon products is an important way to realize solar energy utilization and CO 2 An effective way to recycle resources. Synthesis gas is an important raw material for modern chemical industry such as Fischer-Tropsch synthesis. CO, as the main component of synthesis gas, is not only a common fuel, but also an important raw material for the subsequent synthesis of high value-added chemical products. Therefore, the use of photocatalytic reaction to achieve CO 2 The targeted conversion to CO is of great significance.

[0003] CO 2 The thermodynamic stability is high, and it is activated to form CO 2 - The free radical intermediates need to break through a very high thermodynamic energy barrier. From a kinetic point of view, CO 2 Photoreduction involves a complex electron transfer process, and there are many types of reduction products, and it is difficult to control the selectivity of directional reduction to CO. 2 Adsorption and CO 2 The photocatalyst formed by the intermediate of -CO is the key technology to solve the above problems. Bimetallic oxide materials are the most suitable materials for photocatalytic CO 2 One of the hottest materials for reduction, its CO 2 However, bimetallic oxides still face related technical difficulties, mainly due to their limited charge separation efficiency, the intrinsic conductivity of the material and the high conductivity of CO. 2 There is a contradiction in the optimization process between the adsorption and activation capabilities, and the easy deactivation during long-term illumination and reaction leads to poor durability and cycle stability. 2 When using catalysts for reduction to CO, there is still the problem of low catalyst activity, making it difficult to significantly increase the CO generation rate. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for synthesizing a crystalline / amorphous cobalt manganese oxide catalyst, which can synthesize a crystalline / amorphous mixed phase cobalt manganese oxide, which can be used as a photocatalytic CO 2 When the catalyst for reducing to CO is used, it has good photocatalytic activity and can effectively increase the CO production rate per unit time.

[0005] Technical solution: The synthesis method of the crystalline / amorphous cobalt manganese oxide catalyst of the present invention is specifically as follows: cobalt acetylacetonate and manganese acetylacetonate are used as metal precursors, and alkali metal salt is used as a reaction aid. After mixing them evenly, they are placed under high temperature for calcination. After calcination, the obtained product is washed and dried to obtain crystalline / amorphous CoMnO x ; wherein the calcination temperature is between the melting points of the metal precursor and the alkali metal salt.

[0006] When the calcination temperature is between the melting points of the metal precursor and the alkali metal salt, the acetylacetonate will decompose to produce oxides and form a two-dimensional nanosheet structure along the surface of the unmelted inorganic salt. At the same time, in this case, the alkali metal can effectively reduce the atomic dispersion rate, inhibit the accumulation of atoms into the crystalline state, and induce amorphization.

[0007] The added mass ratio of cobalt acetylacetonate and manganese acetylacetonate is 3:1; the added mass relationship of the metal precursor and the alkali metal salt is that the alkali metal salt should be excessive.

[0008] Wherein, the alkali metal salt is a nitrate; preferably sodium nitrate.

[0009] Wherein, the calcination temperature is 380-400°C.

[0010] The calcination atmosphere is air, the heating rate is 5 to 5.5°C / min, and the heating time is 1 to 1.5 hours.

[0011] Wherein, the washing is performed by washing with deionized water for 3 to 5 times; the drying temperature is 60 to 70° C. and the drying time is 10 to 12 hours.

[0012] The crystalline / amorphous cobalt manganese oxide catalyst prepared by the above synthesis method is used in photocatalytic CO 2 Application in CO reduction.

[0013] The specific application process is as follows: the reaction solution is acetonitrile / triethanolamine / water solution (the mixed volume ratio of acetonitrile, triethanolamine and water is 2:1:2), the concentration of the catalyst in the reaction solution is 2 mg / mL; the reaction light source is a 300W xenon lamp; the reaction system is in a vacuum state before the reaction, and the reactor temperature is controlled at 15°C by circulating cooling water during illumination; high-purity CO is blown in before illumination begins. 2 As reaction raw material.

[0014] The catalyst prepared by the present invention takes into account the advantages of both the crystalline phase and the amorphous phase, and can achieve efficient photocatalytic CO 2On the one hand, the high conductivity and thermodynamic stability of the crystalline phase can effectively realize the separation and transfer of electrons and holes under light conditions; on the other hand, the abundant surface dangling bonds and unsaturated coordinated atoms in the amorphous phase provide CO 2 It provides efficient active sites for adsorption and activation.

[0015] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the crystalline / amorphous cobalt manganese oxygen catalyst prepared by the synthesis method of the present invention has good photocatalytic CO 2 When used in the reduction of CO, it has good photocatalytic activity and catalytic stability, which can effectively increase the CO production rate per unit time, thereby greatly increasing CO 2 -Photocatalytic conversion efficiency of CO. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Preparation of CoMnO with different crystallinity for Example 1 and Comparative Examples 1-2 x Transmission electron microscope image of the material and the corresponding selected area electron diffraction pattern;

[0017] Figure 2 The crystalline / amorphous CoMnO prepared in Example 1 x (CoMnO x -400) high-resolution transmission electron microscopy images, selected area electron diffraction images and elemental imaging images;

[0018] Figure 3 CoMnO with different crystallinity prepared in Example 1 and Comparative Examples 1-2 x X-ray diffraction (a) and X-ray photoelectron spectroscopy (bd) of the material;

[0019] Figure 4 CoMnO with different crystallinity prepared in Example 1 and Comparative Examples 1-2 x Photocatalytic carbon dioxide reduction rate diagram of materials (a), CoMnO x -400 cycle stability diagram (b), CoMnO x -400 isotope calibration analysis diagram (c), CoMnO x -400 catalytic performance under different reaction conditions (d), in-situ infrared spectrum of CoMnOx-400 under light conditions (e);

[0020] Figure 5 CoMnO with different crystallinity x UV-diffuse reflectance absorption spectrum of the material (a), photocurrent response diagram (b), electrochemical impedance diagram (c), and carbon dioxide adsorption capacity test diagram (d);

[0021] Figure 6 Alkali metal salts for CoMnO x Effect of morphology, crystal phase and catalytic performance; (a) is the thermogravimetric analysis of the reagents used in Example 1; (b, c) are the CoMnO prepared in Comparative Example 3 x Electron microscope images of the materials; (d) CoMnO prepared in Example 1 and Comparative Example 3 x Photocatalytic CO 2 Restore performance comparison. DETAILED DESCRIPTION

[0022] Example 1

[0023] The synthesis method of the crystalline / amorphous cobalt manganese oxide catalyst of the present invention is specifically as follows: 6 mg of cobalt acetylacetonate, 2 mg of manganese acetylacetonate and 150 mg of sodium nitrate are ground in an agate mortar for 10 minutes until the powders are fully mixed; then the mixture in the agate mortar is transferred to an open porcelain boat, and calcined in a tube furnace at 400° C. for 1 hour (heating rate of 5° C. / min), and the calcination atmosphere is air; after the sample is naturally cooled to room temperature, the obtained product is washed with deionized water several times and then placed in an oven for drying at 60° C.; a crystalline / amorphous cobalt manganese oxide catalyst is obtained, which is marked as CoMnO x -400.

[0024] Comparative Example 1

[0025] A method for synthesizing an amorphous cobalt manganese oxide catalyst comprises the following steps: grinding 6 mg of cobalt acetylacetonate, 2 mg of manganese acetylacetonate and 150 mg of sodium nitrate in an agate mortar for 10 min until the powders are fully mixed; then transferring the mixture in the agate mortar to an open porcelain boat, calcining the mixture in a tube furnace at 260° C. for 1 h (heating rate of 5° C. / min) in an air atmosphere; after the sample is naturally cooled to room temperature, washing the obtained product with deionized water for several times and then drying the product in an oven at 60° C.; obtaining an amorphous cobalt manganese oxide catalyst, which is marked as CoMnO x -260.

[0026] Comparative Example 2

[0027] A method for synthesizing a crystalline cobalt manganese oxide catalyst comprises the following steps: grinding 6 mg of cobalt acetylacetonate, 2 mg of manganese acetylacetonate and 150 mg of sodium nitrate in an agate mortar for 10 min until the powders are fully mixed; then transferring the mixture in the agate mortar to an open porcelain boat, calcining the mixture in a tube furnace at 500° C. for 1 h (heating rate of 5° C. / min) in an air atmosphere; after the sample is cooled naturally to room temperature, washing the obtained product with deionized water for several times and then drying the product in an oven at 60° C.; obtaining a crystalline cobalt manganese oxide catalyst, which is marked as CoMnOx -500.

[0028] Comparative Example 3

[0029] A preparation method of a cobalt manganese oxide catalyst comprises the following steps: grinding 6 mg of cobalt acetylacetonate and 2 mg of manganese acetylacetonate in an agate mortar for 10 minutes until the powders are fully mixed; then transferring the mixture in the agate mortar to an open porcelain boat, calcining the mixture in a tube furnace at 400° C. for 1 hour (heating rate of 5° C. / min) in an air atmosphere; after the sample is cooled naturally to room temperature, washing the obtained product with deionized water for several times and then drying it in an oven at 60° C.; obtaining crystalline cobalt manganese oxide nanoparticles, labeled as CoMnO x -400(without NaNO 3 ).

[0030] Figure 1 CoMnO with different crystallinity x Transmission electron microscopy and selected area electron diffraction patterns of the material. Figure 1 It can be seen that different crystallinity CoMnO x It presents a structure similar to a two-dimensional nanosheet, and the light spot shown in the selected area electron diffraction is gradually getting brighter, indicating that the crystallinity is gradually increasing.

[0031] Figure 2 The crystalline / amorphous CoMnO prepared in Example 1 x (CoMnO x -400) high-resolution transmission electron microscopy, selected area electron diffraction and corresponding element imaging analysis. Figure 2 It can be seen that CoMnO x The high-resolution electron microscope image at -400 shows a crystalline area with a clear lattice and an amorphous area without a lattice, which means that the material has both amorphous and crystalline structures. The corresponding amorphous area shows a dim diffraction spot, while the crystalline area shows a bright diffraction spot, further indicating that the material has both crystalline and amorphous structures. Elemental analysis shows that the catalyst is mainly composed of Co, Mn, and O elements, and uniform element signals appear on the surface, indicating that Co, Mn, and O elements are uniformly dispersed inside the material.

[0032] Figure 3 CoMnO with different crystallinity x X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) diagrams. Figure 3 From the XRD data, we can see that CoMnO x Basic phase structure of materials and MnCo 2 O 4.5In addition, the gradual sharpening of the XRD diffraction peak indicates that the crystallinity is gradually increasing. From the XPS data of different crystal phases, it can be seen that the prepared materials can maintain the stability of the surface chemical structure on the basis of different crystallinity. CoMnO x In the material, Co mainly exists in divalent and trivalent forms, Mn mainly exists in trivalent and tetravalent forms, and O exists in the form of adsorbed O and lattice O.

[0033] Figure 4 CoMnO with different crystallinity x Photocatalytic CO 2 Reduction efficiency diagram. Figure 4 It can be seen that CoMnO x The catalysts all have CO 2 Photoreduction activity of CoMnO with crystalline / amorphous structure x The performance is the best, with a CO production rate of 146.09 μmol / g / h (selectivity 93.58%). Figure 4 b shows that amorphous / crystalline CoMnO x -400 has good CO 2 Reduction stability. Figure 4 d CoMnO x The catalytic performance of -400 under different reaction conditions shows that without catalyst, without light, without CO 2 None of them can effectively produce CO, indicating that the CO detected in the system is obtained through a complete photocatalytic process. Figure 4 eCoMnO x -400 in situ infrared spectra under light conditions (used to monitor the transformation path of molecules) show that under light irradiation, CoMnO x -400 catalyst at 1223cm -1 The absorption peak at is attributed to *CO 2 - The bending vibration of the generated *CO 2 - Indicates CO 2 The molecules are CoMnO x -400 adsorbed on the catalyst surface and activated; at 1452cm -1 and 1406cm -1 The two peaks at 3 2- Symmetrical stretch. 1640cm -1 、1326cm -1 and 1279cm -1 The three peaks at *COOH belong to the stretching of C=O, the stretching of CO, and the deformation of OH, which are considered to be CO2 The important reaction intermediates in the reduction process to CO have a strong increasing trend, which also indicates that the dominant product formed in the whole reaction process is CO.

[0034] Figure 5 CoMnO with different crystallinity prepared in Example 1 x Analysis chart of physical and chemical properties. Figure 5 It can be seen that CoMnO x It has a spectral absorption range that responds to the entire visible light region. Figure 5 b shows that crystalline / amorphous CoMnO x -400 shows good photoelectric response efficiency. Figure 5 c shows that crystalline / amorphous CoMnO x -400 shows the lowest resistance. Figure 5 d shows that with the increase of material crystallinity, CoMnO x CO 2 The adsorption amount gradually decreased.

[0035] Figure 6 The alkali metal salt in Example 1 is x The influence of morphology, crystal phase and catalytic performance. Figure 6 a It can be seen that the melting point of alkali metals is higher than that of metal precursors. Figure 6 b It can be seen that without adding NaNO 3 When the reaction aid is used, the obtained CoMnO x It is a blocky particle structure rather than a nanosheet structure. Figure 6 c shows that without adding NaNO 3 When the reaction aid is used, the obtained CoMnO x It is a crystalline phase rather than an amorphous / crystalline mixed phase. Figure 6 d shows that adding NaNO 3 The amorphous / crystalline mixed phase CoMnO obtained in the case of a reaction aid x -400 catalyst performs much better than without adding NaNO 3 CoMnO prepared under x -400.

[0036] The catalysts of Example 1 and Comparative Examples 1 to 3 were subjected to photocatalytic CO 2 The application of reduction to produce CO, the specific application process is:

[0037] The photocatalytic carbon dioxide reduction reaction was carried out in a commercially available online detection system (CEL-SPH2N, China Education Au-Light, Beijing). The photocatalyst dosage was 10 mg; the reaction solution was 5 mL of acetonitrile / triethanolamine / water solution (volume ratio of 2:1:2); the reaction light source was a 300 W xenon lamp (CEL-HX F300 / CEL-HX UV300, China Education Au-Light, Beijing), without a filter.

[0038] The reaction system should be in a vacuum state before the reaction. During the illumination, the temperature of the reactor is controlled at 15°C by circulating cooling water. Before the illumination begins, equal amounts of high-purity CO 2 As the reaction raw material, the reaction was carried out for 5 hours. The gas chromatograph (GCD7920P) was used with TCD, FID detector and The carbon monoxide and hydrogen production were analyzed using a molecular sieve column (Ar as carrier gas).

[0039] pass Figure 4 a and Figure 6 d shows that CoMnO with crystalline / amorphous structure x -400 has the best performance, with a CO production rate of 146.09 μmol / g / h (selectivity 93.58%), which is far superior to the performance of the catalysts prepared in Comparative Examples 1 to 3.

Claims

1. A method for synthesizing a crystalline / amorphous cobalt-manganese-oxygen catalyst, characterized in that: Specifically, cobalt acetylacetonate and manganese acetylacetonate are used as metal precursors, and alkali metal salts are used as reaction aids. After being mixed evenly, they are placed under high temperature for calcination. After calcination, the obtained product is washed and dried to obtain crystalline / amorphous CoMnO x ; wherein the calcination temperature is between the melting points of the metal precursor and the alkali metal salt.

2. The method for synthesizing the crystalline / amorphous cobalt manganese oxygen catalyst according to claim 1, characterized in that: The added mass ratio of cobalt acetylacetonate to manganese acetylacetonate is 3:

1.

3. The method for synthesizing the crystalline / amorphous cobalt manganese oxygen catalyst according to claim 1, characterized in that: The alkali metal salt is a nitrate.

4. The method for synthesizing the crystalline / amorphous cobalt manganese oxygen catalyst according to claim 3, characterized in that: The calcination temperature is 380-400°C.

5. The method for synthesizing the crystalline / amorphous cobalt manganese oxygen catalyst according to claim 4, characterized in that: The calcination atmosphere is air, the heating rate is 5-5.5°C / min, and the heating time is 1-1.5h.

6. The method for synthesizing the crystalline / amorphous cobalt manganese oxygen catalyst according to claim 1, characterized in that: The washing is performed by washing with deionized water for 3 to 5 times; the drying temperature is 60 to 70° C. and the drying time is 10 to 12 hours.

7. Use of the crystalline / amorphous cobalt manganese oxygen catalyst prepared by the synthesis method of claim 1 in photocatalytic CO2 reduction to produce CO.

8. The use according to claim 7, characterized in that: The specific application process is as follows: the reaction solution is acetonitrile / triethanolamine / water solution, in which the concentration of the catalyst is 2 mg / mL; the reaction light source is a 300W xenon lamp; and high-purity CO2 is blown in as a reaction raw material before illumination begins.

9. The use according to claim 8, characterized in that: The mixing volume ratio of acetonitrile, triethanolamine and water is 2:1:

2.

10. The use according to claim 8, characterized in that: The reaction system was in a vacuum state before the reaction, and the temperature of the reaction system was 15°C during the illumination.